Glymphatic System Dysfunction: A Novel Mediator of Sleep Disorders and Headaches - Yi, Ting; Gao, Ping; Zhu, Tianmin; Yin, Haiyan; Jin, Shuoguo (Frontiers in Neurology, 2022)
Sleep contributes to the maintenance of overall health and well-being. There are a growing number of patients who have headache disorders that are significantly affected by poor sleep. This is a paradoxical relationship, whereby sleep deprivation or excess sleep leads to a worsening of headaches, yet sleep onset also alleviates ongoing headache pain. Currently, the mechanism of action remains controversial and poorly understood. The glymphatic system is a newly discovered perivascular network that encompasses the whole brain and is responsible for removing toxic proteins and waste metabolites from the brain as well as replenishing nutrition and energy. Recent studies have suggested that glymphatic dysfunction is a common underlying etiology of sleep disorders and headache pain. This study reviews the current literature on the relationship between the glymphatic system, sleep, and headaches, discusses their roles, and proposes acupuncture as a non-invasive way to focus on the glymphatic function to improve sleep quality and alleviate headache pain.